The Christian Approach to Divine Creation in the Context of Scientific Worldview - Słomka, Marek (Religions, 2025)
The paper examines the main components of the Christian view of creation in light of a scientific worldview. Although no scientific theory can refute or corroborate the doctrine of creation, the current state of natural sciences does have some impact on the formation of creationism. The author underlines this influence and depicts the importance of a rational and aspectual approach to the Christian idea of creation and the Creator–creation relationship. The concept of creation is also presented as having significant consequences for the expression of various elements of religious doctrine, including the place of man in the world.